D & S Ausstellung. (Hamburg : Kunstverein in Hamburg, 1989)
ABR Stuttgart ; Adams, Dennis ; Armaly, Fareed ; Armleder, John M. ; Art in Ruins ; Asher, Michael ; Belcher, Alan ; Bickerton, Ahley ; Bidlo, Mike ; Bosslet, Eberhard ; Cazal, Philippe ; Deleu, Luc ; Dellbrügge/De Moll ; Demary, Stefan ; Ecker, Bogomir ; General Idea ; Ginkel, Andreas ; Görlich, Ulrich ; Gries, Gero ; Group Material ; Grünfeld, Thomas ; Höller, Carsten ; Holzer, Jenny ; IFP ; Ingold, Res ; Kliaving, Serge ; Koons, Jeff ; Kosolapov, Alexander ; Kunzmann, Thomas ; Lavier, Bertrand ; Leccia, Angel ; Lum, Ken ; Müller, Harald F. ; Multi Geräte ; Mundt, Wilhelm ; Opie, Julian ; Pallanca, Heike ; Polke, Sigmar ; Presence Panchounette ; Prince, Richard ; Radermacher, Norbert ; Rahayel, Claudia ; Raynaud, Patrick ; Rheinsberg, Raffael ; Robbe, Wolfgang ; Robbins, David ; Rohling, Gerd ; Schaerf, Eran ; Silver, Shelly ; Slominski, Andreas ; Steinbach, Haim ; Stille Helden e.V. ; Sturtevant, Elaine ; Tillmann/Vollmer ; Turek, Jeff ; Vilmouth, Jean-Luc
D & S Ausstellung, Kunstverein in Hamburg, 14. Oktober - 26. November 1989
boek